2009
DOI: 10.1095/biolreprod.108.071951
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Developmental Disorders of the Rat Penis Involve Both Estrogen Receptor (ESR)- and Androgen Receptor (AR)-Mediated Pathways1

Abstract: This study tested the hypothesis that the estrogen receptor (ESR) pathway, androgen receptor (AR) pathway, or both mediate estrogen-induced developmental penile disorders. Rat pups received diethylstilbestrol (DES), with or without the ESR antagonist ICI 182,780 (ICI) or the AR agonist dihydrotestosterone (DHT) or testosterone (T), from Postnatal Days 1 to 6. Testicular T concentration, penile morphology and morphometry, and/or fertility was determined at age 7, 28, or 150 days. DES treatment alone caused 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…The support for a direct effect comes from observations that estrogen receptors are present in the rat penis at birth [38] and from our observations that estrogen-induced penile maldevelopment was associated with ESR1 up-regulation [39] and was mitigated by ESR antagonist ICI coadministration with estrogen [24]. ESR1 up-regulation was associated with abnormal development of the female reproductive tract [40], mammary gland [41], prostate [42], and seminal vesicles [43] in rodents treated neonatally with estrogens.…”
Section: Estrogen-reduced Myh11 Expression In the Penismentioning
confidence: 60%
See 4 more Smart Citations
“…The support for a direct effect comes from observations that estrogen receptors are present in the rat penis at birth [38] and from our observations that estrogen-induced penile maldevelopment was associated with ESR1 up-regulation [39] and was mitigated by ESR antagonist ICI coadministration with estrogen [24]. ESR1 up-regulation was associated with abnormal development of the female reproductive tract [40], mammary gland [41], prostate [42], and seminal vesicles [43] in rodents treated neonatally with estrogens.…”
Section: Estrogen-reduced Myh11 Expression In the Penismentioning
confidence: 60%
“…Previously, we reported that adult rats treated neonatally with the antiandrogen GnRH-antagonist [23] or estrogens [24,25] developed similar penile abnormalities, including loss of cavernous spaces and accumulation of fat cells. These abnormalities occurred in animals that were treated with DES before 12 days of age but not after.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations